The rise of the network society - Castells, Manuel (Blackwell Publishers Inc., 1996)
This book is an account of the economic and social dynamics of the new age of information. Based on research in the USA, Asia, Latin America, and Europe, it aims to formulate a systematic theory of the information society which takes account of the fundamental effects of information technology on the contemporary world.